Impact of functional synapse clusters on neuronal response selectivity - Balázs B. Ujfalussy (Nature Portfolio, 2020)
The formation of functional synaptic clusters (FSCs) and their impact on somatic membrane potential (sVm) in vivo are poorly understood. Here, the authors develop a computational approach to show that FSCs have to form via local rather than global plasticity and be moderately large to impact sVm.